2013
DOI: 10.1371/journal.pone.0065943
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphate Source Influences Gene Expression and Quality of Mineralization during In Vitro Osteogenic Differentiation of Human Mesenchymal Stem Cells

Abstract: For in vitro differentiation of bone marrow-derived mesenchymal stem cells/mesenchymal stromal cells into osteoblasts by 2-dimensional cell culture a variety of protocols have been used and evaluated in the past. Especially the external phosphate source used to induce mineralization varies considerably both in respect to chemical composition and concentration. In light of the recent findings that inorganic phosphate directs gene expression of genes crucial for bone development, the need for a standardized phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 50 publications
6
45
0
Order By: Relevance
“…This finding was confirmed by molecular analysis, since the low oxygen tension promoted the expression of noncollagenous and collagenous proteins which are related to the MSC differentiation and mineralization [Granchi et al, ]. In addition, the up‐regulation of ALPL transcripts suggests that the mineralization process is facilitated by hypoxic conditions [Schäck et al, ].…”
Section: Discussionmentioning
confidence: 87%
“…This finding was confirmed by molecular analysis, since the low oxygen tension promoted the expression of noncollagenous and collagenous proteins which are related to the MSC differentiation and mineralization [Granchi et al, ]. In addition, the up‐regulation of ALPL transcripts suggests that the mineralization process is facilitated by hypoxic conditions [Schäck et al, ].…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, investigating the physicochemical properties of CaP nanoparticles and their possible interactions with BMSCs will likely broaden our understanding of high Pi-related bone impairment in vivo. In this study, the concentration of Pi was based on that used in the literature [5,12,13]. Our results indicated that CaP nanoparticles formed in culture media were associated with the process of high Pi mediated osteogenic differentiation BMSCs and the physicochemical properties of CaP nanoparticles played an important role in modulating the biological response of BMSCs.…”
Section: Introductionmentioning
confidence: 83%
“…Cells were cultured in 50% DMEM (Gibco, Gaithersburg, MD, USA) and 50% F12 (Gibco) with 5% FBS. Differentiation to chondrocytes was performed over 6 days with ascorbic acid (50 μg/mL) and increasing concentrations of NaH 2 PO 4 0.5mM, 1mM, and 2mM as described . Human microvascular endothelial cells (HMVECs) were purchased from Cell Systems (Kirkland, WA, USA) and cultured in EGM2‐MV medium (Lonza, Walkersville, MD, USA) with 5% FBS and 1% antibiotics in an incubator with 5% CO 2 at 37°C.…”
Section: Methodsmentioning
confidence: 99%